43 Pre primary percutaneous coronary intervention timi flow grades in stemi patients pre-loaded with ticagrelor. (October 2018) - Jan, Z; Ullah, I; Ibrahim, M; Kiernan, T
Abstract : Background: Ticagrelor, a potent P2Y12 receptor inhibitor, is recommended along with Aspirin as initial therapy for ST Segment Elevation Myocardial Infarction (STEMI).19 Whether Ticagrelor can improve coronary patency before Primary percutaneous coronary (PPCI) intervention in STEMI patients is not well known. Our aim was to analyse initial TIMI (Thrombolysis In Myocardial Infarction) flow grades in infarct related artery (IRA) in STEMI patients preloaded with Ticagrelor who presented to our unit between January 1st 2016 and December 31st 2017. Methods: We retrospectively conducted this single centre observational study after spotting STEMI patients using heart beat and HIPE (Hospital in patient enquiry) data bases. We reviewed their hospital notes and coronary angiograms. We analysed TIMI flow grades in the infarct related artery (IRA) on initial angiography prior to any intervention. The primary end point was the comparison between the proportion of patients who did not have TIMI flow grades I-III in the IRA at initial angiography in the prehospital and in-hospital ticagrelor treated patients. Multivariate statistical analysis was performed using SPSS-22. Results: A total of 328 patients with STEMI who received Ticagrelor prior to arrival in the catheterization laboratory were enrolled, 258 were given Ticagrelor pre hospital (by ambulance crew or in other Hospital) and 70 in the Hospital (In the emergency department or in catheter laboratory). 62 (18.90%) were females and 266 (81.10%) males. Mean age was 62.78±11.85 years range 31–91 years. TIMI flow grade 0, I, II and III were 57%, 7.8%, 7.8% and 27.5% respectively in the pre hospital Ticagrelor treated and 71.4%, 10%, 4.3% and 14.3% in the In hospital Ticagrelor treated patients. TIMI flow grades I-III were 43% and TIMI flow grade 0 at 57% in the pre hospital Ticagrelor treated, while TIMI flow grade I-III were 28.6% and TIMI flow grade 0 was 71.4% respectively in patients who were given Ticagrelor in the Hospital (p=0.029). Conclusions: Our findings of better pre intervention TIMI flow grades I-III in STEMI patients pre-treated with Ticagrelor in the field suggests that Ticagrelor appears to improve pre intervention coronary reperfusion in the Infarct related artery (IRA) in STEMI patients.